2019
DOI: 10.3347/kjp.2019.57.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey on Schistosomiasis and Intestinal Helminthiasis among Village Residents of the Rural River Basin Area in White Nile State, Sudan

Abstract: There have been some reports on schistosomiasis of school children in Sudan’s Nile River basin area; however, information about the infection status of Schistosoma species and intestinal helminths among village residents of this area is very limited. Urine and stool samples were collected from the 1,138 residents of the Al Hidaib and Khour Ajwal villages of White Nile State, Sudan in 2014. The prevalence of overall schistosomiasis and intestinal helminthiasis was 36.3% and 7.7%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Prior to the baseline survey of this study, SACs in Al Jabalain had received MDA interventions twice during the 4 years of the 1st phase of the KOICA project, while those in El Salam had not. In 2013, the baseline prevalence of S. haematobium infection was 35.2% in El Salam, which was similar to that in previous studies in the White Nile State [5,6,22], while the 2013 baseline prevalence in Al Jabalain was 9.1% due to previous MDA intervention within 4 years [5]. In this study, the reduction in the prevalence of infection after MDA was 80.3% in Al Jabalain and 84.4% in El Salam.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Prior to the baseline survey of this study, SACs in Al Jabalain had received MDA interventions twice during the 4 years of the 1st phase of the KOICA project, while those in El Salam had not. In 2013, the baseline prevalence of S. haematobium infection was 35.2% in El Salam, which was similar to that in previous studies in the White Nile State [5,6,22], while the 2013 baseline prevalence in Al Jabalain was 9.1% due to previous MDA intervention within 4 years [5]. In this study, the reduction in the prevalence of infection after MDA was 80.3% in Al Jabalain and 84.4% in El Salam.…”
Section: Discussionsupporting
confidence: 85%
“…Human schistosomiasis caused by S. haematobium is one of the major public health concerns in Sudan. Previous studies showed that the prevalence of S. haematobium infection in the White Nile State of Sudan was 28.5% [ 5 ], 45.0% [ 6 ], 21.9% [ 21 ], and 35.6% [ 22 ] in different survey areas and times. In this study, we compared changes in the prevalence and intensity of S. haematobium infection between Al Jabalain and El Salam districts of White Nile State before and after MDA intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Sudanese government prioritised collecting data on the burden of NTDs, particularly schistosomiasis. In response; many epidemiological studies were conducted in central and east Sudan (10,11), with relatively few, if any, such studies being conducted in Darfur area.…”
Section: Discussionmentioning
confidence: 99%
“…The urine samples were rst observed whether show occult or gross hematuria, and then examined for the presence of S. haematobium eggs by membrane ltration technique as described previously [10]. In brief: all urine samples of su cient quantity were shaken, subsequently, 10 ml of each sample were pressed through a polycarbonate lter with a pore size of 20 µm (Sterlitech, Kent, WA, USA) using a standard 10 ml plastic syringe, the membrane was then put on a microscope slide, covered with a piece of hydrophilic cellophane soaked in glycerol solution, and examined under the microscope by trained laboratory technicians using some drops of Lugol's iodine to stain S. haematobium eggs after cellophane coverage.…”
Section: Laboratory Investigationmentioning
confidence: 99%
“…The highest prevalence of SCH infection of the reviewed articles [14,24,[28][29][30][31] was seen in Tanzania [14].…”
Section: Introductionmentioning
confidence: 99%